(untitled) (De Legibus - Law Journal, 2024)
The present study analyzes the types of knowledge and the methods that correspond to them, as instruments for discovering the truth. The resolution of problems and conflicts of interest requires advanced training from the jurist in the different fields of activity, enabling him to define objectives and choose the most effective paths to obtain answers. Using the appropriate method is the key to success in the investigation. How to choose and delimit the research topic, how to define the subject or problem, how to respect the principles of ethics and transparency whenever knowledge from other authors is used, what precautions should be taken in citations, preparation and presentation of work are fundamental questions that we seek to answer in this study.